1993
DOI: 10.1046/j.1523-1739.1993.07010122.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Problems in Conservation Genetics Using Captive Drosophila Populations: Consequences of Equalization of Family Sizes

Abstract: Equalization of family sizes is recommended for use in captive breeding programs, as it is predicted to double effective population sizes, reduce inbreeding, and slow the loss of genetic variation. The effects of maintaining small captive populations with equalization of family sizes versus random choice of parents on levels of inbreeding genetic variation, reproductive fitness, and effective population sizes (Ne) were evaluated in 10 lines of each treatment maintained with four pairs of parents per generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 23 publications
5
43
1
Order By: Relevance
“…This occurred in an experiment where we were comparing replicated populations designed to have the same effective sizes, but maintained using equal vs. variable family sizes on medium with CuSO 4 added . Prior experiments under benign conditions yielded rates of inbreeding in accord with design expectations (Borlase et al, 1993), but in the stressful environment with CuSO 4 , the inbreeding coefficient was elevated by approximately 50% in the variable family size treatment. The elevated level of inbreeding on the stressful medium was because of higher family size variation in the stressful environment than under benign conditions (R. Frankham & H. Manning, unpublished data).…”
Section: Inbreeding Loss Of Genetic Diversity Stress and Extinctionmentioning
confidence: 59%
“…This occurred in an experiment where we were comparing replicated populations designed to have the same effective sizes, but maintained using equal vs. variable family sizes on medium with CuSO 4 added . Prior experiments under benign conditions yielded rates of inbreeding in accord with design expectations (Borlase et al, 1993), but in the stressful environment with CuSO 4 , the inbreeding coefficient was elevated by approximately 50% in the variable family size treatment. The elevated level of inbreeding on the stressful medium was because of higher family size variation in the stressful environment than under benign conditions (R. Frankham & H. Manning, unpublished data).…”
Section: Inbreeding Loss Of Genetic Diversity Stress and Extinctionmentioning
confidence: 59%
“…Experiments, particularly, involving Drosophila (Loebel et al, 1992;Borlase et al, 1993, Montgomery et al, 1997 have demonstrated the advantages of equalising the contributions of individuals, rather than producing a random number of offsprings. A recent study by Rodríguez-Ramilo et al (2006) assessed the effect of conservation strategies on the accumulation of deleterious mutations.…”
Section: Practical Applications Of Pedigree-based Managementmentioning
confidence: 99%
“…This has both positive and negative a priori consequences. On the positive side, because selection is minimized, adaptation to captivity is also reduced (Allendorf 1993;Frankham et al 2000), and this is something desirable when the final objective of a conservation program is the reintroduction of the captive population into the wild (Loebel et al 1992;Borlase et al 1993;Couvet and Ronfort 1994;Frankham et al 2000). On the negative side, the reduced purifying selection implies that many deleterious genes segregating in the base population and new mutations appearing during the program will more likely be fixed, with the corresponding consequences on the reproductive capacity of the individuals (see Bryant and Reed 1999).…”
mentioning
confidence: 99%